Simulation method of shortest and safest path algorithm for evacuation in high rise building - Mohd Sabri, Nor Amalina; Hasan Basari, Abd Samad; Hussin, Burairah; Abu Samah, Khyrina Airin Fariza (Hikari Ltd, 2014)
The objectives of this research are to identify the suitable shortest and safest path algorithm for evacuation, and followed by design and develop an evacuation preparedness model simulation via shortest path algorithm to choose a suitable exit route to evacuate the evacuees. These objectives have been carried out to overcome the problem of difficulties faced by the evacuees to find the best routes including shortest and safest path. Five steps of methods are brought out to achieve the objectives by implementing the Dijkstra Algorithm. The first step is importing the matrix data followed by input the source and destination ID. Third step is to generate the shortest path, the fourth is removed the edges and finally generate the safest path. This research is concentrating on high rise building during critical incident and evacuation. The preliminary result has shown an encouraging result which can provide the shortest and safest path for the evacuees.